Study of Possible Correlation between Pancreatitis and Daily Consumption of Catha edulis in Experimental Animals - Battah, Mohamed M. Rezq; Ibrahim, Doa'a Anwar; Shamsher, Amani M. (Journal of Drug Discovery and Therapeutics, 2015)
Khat (Catha edulis) is widely used throughout the world especially in Yemen and East Africa; It becomes a serious public health phenomena in Yemen that affects the health features of life. The present study evaluates the possible correlation between pancreatitis and daily consumption of khat leaves or extract in rabbits. Thirty adult male rabbits were divided randomly into five groups, 6 each: (I)control, (II)L-arginine, (III)pioglitazone, (IV)khat leaves and (V)khat extract. From group (II) to (V) were given L-arginine (450mg/100g b.wt) i.p to induce acute pancreatitis. Treatments were given via oral gavage for 4 weeks. FBS, p.amylase, lipase, insulin, TAS were measured as well as histopathology examination of pancreas. FBS was significantly reduced, whereas insulin level was increased in both groups of khat (leaves and extract). Additionally, p.amylase and lipase levels were decreased, and increased in TAS level. These results similar to that in pioglitazone group compared to L-arginine group, which found that significantly increased in p.amylase, lipase and FBS, while decreased in insulin and TAS levels. All these were accompanied with pancreatic histopathological improvements seen in khat leaves, khat extract and pioglitazone groups when compared to L-arginine group. The improvement of acute pancreatitis induced by L-arginine reflected remarkably on FBS and insulin levels in khat treated groups, this indicating that there is no correlation between acute pancreatitis and daily consumption of khat.